Формирование инновационной стратегии региональной холдинговой организации сферы услуг (Путеводитель предпринимателя)
The article examines the problems of developing strategies for implementation and dissemination of innovations in the regional horizontal holding company services. A model of the basic strategies of diffusion of innovation, which allows for a reasonable choice of strategy depends on the internal competencies and external market opportunities for regional services.